Research awareness among dental undergraduates; A cross-sectional study conducted at Karachi Medical and Dental College, Karachi - Kashif, Mehwash; Zareef, Uzma; Aftab, Mehreen; Irfan Khan, Sadia; Abul Barakat, Afifia (International Journal of Endorsing Health Science Research, 2020)
Background: Research is an integral part of the academic curriculum; its role must be appreciated in all health and medical field. The current study was planned in order to evaluate the interest of dental students towards research and their awareness. Methodology: A cross-sectional study was conducted from June to December 2018 at Karachi Medical and Dental College (KMDC). A total of 200 bachelors of dental surgery (BDS) students were recruited as per the inclusion criteria. Non-consenting students were excluded from the study. Data regarding research understanding and awareness was collected and analyzed using SPSS Version 17.0. Results: Majority of the study participants were female 89% and males 11%, females were in high proportion among all professional years. i.e. 27%, 21%, 25.5% & 15.5% from 1st year to 4th year respectively. Mostly the 2nd & 3rd year students were aware of the research needs 97.7% and 100%. The research interest was most among the students of the initial years while among 4th years students it was comparatively less i.e. 78.3%. All of the students from 1st year to 3rd responded in favor of research usefulness in career while only 67.5% of the final year students were lacking this basic knowledge. Moreover, the benefits of research were well known among students of all years with the highest understanding among the 2nd and 3rd year (97.7% and 94.4%). Conclusion: It is evident from the study results that the enrolled dental students were aware of research significance, its professional importance and showed positivity towards research interest. The inclusion and implementation of research among dental students is essential for promoting research culture in medical students.